Induced Pluripotent Stem Cell-Derived Megakaryocytes and Platelets for Disease Modeling and Clinical Use - Borst, Sara (Arterioscler Thromb Vasc Biol, 2017)
Platelets, derived from megakaryocytes, are anucleate cytoplasmic discs that circulate in the blood stream and play major roles in hemostasis, inflammation, and vascular biology. Platelet transfusions are utilized in a variety of medical settings to prevent life-threatening thrombocytopenia due to cancer therapy, other causes of acquired or inherited thrombocytopenia, and trauma. Currently, platelets used for transfusion purposes are donor-derived. However, there is a drive to generate non-donor sources of platelets to help supplement donor-derived platelets. Efforts have been made by many laboratories to generate in vitro platelets and optimize their production and quality. In vitro-derived platelets have the potential to be a safer, more uniform product, and genetic manipulation could allow for better treatment of patients that become refractory to donor-derived units. This review focuses on potential clinical applications of in vitro-derived megakaryocytes and platelets, current methods to generate and expand megakaryocytes from pluripotent stem cell sources, and the use of these cells for disease modeling.